Translating Metaphtonymy: Exploring Trainee Translators' Translation Approaches and Underlying Factors - Jin, Shengxi; Lin, Zhengjun; Oakley, Todd (Frontiers in Psychology, 2021)
Metaphonymy is identified as a special rhetoric figure that specifies the interaction between metaphor and metonymy and which is pervasive in literary works. How and why do trainee translators translate metaphonymy? Using task analysis, semi-structured discourse-based interviews, and a questionnaire survey among 30 MTI (master of translation and interpreting) trainee translators, the study investigates their translation approaches adopted when translating the metaphonymies in Chinese extract prose and explores the effects of their choices. It is found that they mainly employed three approaches: omission, modification, and retainment, with omission being the most-and retainment the least-frequent. The main factors attributing to each approach range from the prominence degrees and cross-cultural adaptation abilities of the metaphonimies, translators’ rhetorical awareness, and transference competence to their translation knowledge sub-competence. The article suggests that trainee translators should be instructed to systematically construct rhetoric knowledge, and teaching design should emphasize trainees' competence of identifying rhetorical devices and their competence of shifting rhetoric between languages.